Barrier Layer Variability in the Central Equatorial Pacific Associated With ENSO Development - Cong Guan; Michael J. McPhaden; Shijian Hu; Fan Wang; Yuanlong Li; Manman Cui (Geophysical Research Letters)
Abstract Previous studies suggest that a thick barrier layer can strengthen surface warming during El Niño and vice versa for La Niña. Here we find barrier layer changes of up to 6 m in the central equatorial Pacific (CEP, 170°E−160°W, 5°S–5°N) in response to a 1°C change in the Niño 3.4 index using 19 years of Argo observations. Our analysis reveals that mixed layer variability due to strong interannual salinity anomalies determines the changes in CEP barrier layer thickness (BLT) during El Niño Southern Oscillation events since isothermal layer variations are minimal there. During El Niño, enhanced rainfall leads to anomalous surface freshening in the CEP especially west of the dateline, while anomalous vertical‐sheared zonal current results in stronger vertical salinity stratification and thicker barrier layer east of the dateline in the CEP. Surface‐layer zonal current advection in general contributes to a thicker barrier layer in the entire CEP.